Au Micro‐ and Nanoelectrodes as Local Voltammetric pH Sensors During Oxygen Evolution at Electrocatalyst‐Modified Electrodes - Lejing Li; Ndrina Limani; Rajini P Antony; Stefan Dieckhöfer; Carla Santana Santos; Wolfgang Schuhmann (Small Science, 2024)
The scarcity of state‐of‐the‐art oxygen evolution reaction (OER) electrocatalysts has led to intensive research on alternative viable electrocatalytic materials. While activity and cost are the main factors to be sought after, the catalyst stability under harsh acidic conditions is equally crucial. Considering that OER is a proton‐coupled electron‐transfer reaction that involves local acidification of the reaction environment by liberation of H+, the catalyst stability can be largely compromised in such conditions. Consequently, probing the pH value near the catalyst surface under operation leads to a deeper understanding of this process. The applicability of bare Au microelectrodes and nanoelectrodes as sensitive local pH probes during OER is shown in this work by using scanning electrochemical microscopy (SECM). Two case studies are presented, including the state‐of‐the‐art OER catalyst (IrO2) in acidic media and a ZnGa2O4 catalyst in alkaline buffered solution, demonstrating the suitability of the Au probe to accurately determine the local pH value in a wide pH range.